Effect of operative local anesthesia on postoperative pain outcomes of inflatable penile prosthesis: prospective comparison of two medications. Issue 3 (June 2018) - Xie, Donghua; Nicholson, Marilin; Azaiza, Mohammed; Gheiler, Victor; Lopez, Isabel; Nehrenz, Guy; Klopukh, Boris; Bianco, Fernando; Perito, Paul; Gheiler, Edward
Abstract Few studies have examined the roles of dorsal penile nerve block (DPNB) and penile ring block (PRB) in surgery of inflatable penile prosthesis (IPP) placement. We sought to compare the postoperative pain outcomes of two different medications used in DPNB plus PRB. We thus carried out a prospective study of patients with erectile dysfunction who underwent "de novo" IPP placement between January 2013 and June 2013. Patients were divided to one of three groups: 1-DPNB plus PRB with bupivacaine injection; 2-DPNB plus PRB with ropivacaine injection and, 3-Control group without DPNB or PRB injection. Postoperative pain score and pain medication usage were recorded 2 h postoperatively, and every 24 h, for a week. The Visual Analog Scale (VAS) was used as pain scale measurement. A total of 131 patients were included in this study: 40 to bupivacaine, 47 to ropivacaine, and the rest were controls. Two hours postoperatively, mean VAS was significantly different (p  < 0.0001) between medicated patients and the control group, however, no significant differences were observed between medication groups. Mean VAS was not significantly different among the groups from post-surgical day 2 thru 7. In conclusion, DPNB plus PRB during IPP provided effective analgesia in the immediate post-operative recovery.